2015
DOI: 10.1371/journal.pone.0120964
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Supplementation of Pomegranates, Figs and Dates Alleviate Neuroinflammation in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a devastating age-related neurodegenerative disease with no specific treatment at present. The APPsw/Tg2576 mice exhibit age-related deterioration in memory and learning as well as amyloid-beta (Aβ) accumulation, and this mouse strain is considered an effective model for studying the mechanism of accelerated brain aging and senescence. The present study was aimed to investigate the beneficial effects of dietary supplements pomegranate, figs, or the dates on suppressing inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 95 publications
3
73
0
Order By: Relevance
“…Another study was made to examine the beneficial effects of dietary supplements containing pomegranate, figs, or the dates on suppressing inflammatory cytokines. Finding confirmed that increased levels of inflammatory cytokines and eotaxin activity were decreased by administration of the diet supplements [54].…”
Section: Nematicidal Activitysupporting
confidence: 52%
“…Another study was made to examine the beneficial effects of dietary supplements containing pomegranate, figs, or the dates on suppressing inflammatory cytokines. Finding confirmed that increased levels of inflammatory cytokines and eotaxin activity were decreased by administration of the diet supplements [54].…”
Section: Nematicidal Activitysupporting
confidence: 52%
“…Both berry-containing diets improved the spatial working memory deficit of aged APdE9 AD mice compared to the corresponding mice fed the control diet, suggesting that anthocyanin-rich bilberry and blackcurrant supplements favorably modulate APP processing and improve behavioral abnormalities in the AD mouse model (Tapias et al, 2014). Long-term oral administration of pomegranate extracts significantly prevented the elevated production of pro-inflammatory cytokines in the serum and brain tissues as well as neuronal contents of Aβ1–40 and Aβ1–42 in a transgenic mouse model of AD (Essa et al, 2015). …”
Section: Translational Research Opportunities and Challengesmentioning
confidence: 99%
“…The current interest in the benefits to human health of antioxidant compounds of fruits has led to many research projects in the field of AD [1]. …”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effects of pomegranate pulp extract were also observed in mouse models of AD, including a decrease in IL-6 and TNF-α in mouse brain samples [1,6]. This effect could contribute to attenuation of progression of the disease, once a prominent chronic inflammatory reaction is observed with the development of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation